A Rapid Method of Separation and Estimation of Squalene from Fish Liver Oils Using Iatros- can Analyser - Thankappan, T.K.; Gopakumar, K. (Fishery Technology, 2025)
Squalene is found present only in Chilloscylliumgriseum liver oil among the four shark liver oils studied. The unsaponifiable matter (80% of oil) contained 71% squalene. The seperation of squalene by column chromatography is discussed. For the quantitative recovery of 1 g of squalene on 10 g alumina column 30 ml petroleum ether is required. The detection of squalene is found to be higher using Iatroscan compared to column chromatography using alumina.